Modal hedging verbs in English as a Lingua Franca (ELF) Business Management research articles - Mur-Dueñas, Pilar (Kalbotyra, 2017)
When publishing the results of their research, scholars need to convince their readers of the validity of their claims, adjusting their writing to the prevailing discursive and rhetorical conventions. Hedges play a crucial role in persuading readers of such validity. Previous cross-cultural research in English for Academic Purposes (EAP) has revealed significant differences in the use of these interpersonal features in research articles (RAs) in different languages and publication contexts. In this paper, hedging modal verbs will be contrastively analysed in a corpus of RAs written by English as a Lingua Franca (ELF) users and by native English scholars affiliated to Anglophone institutions in the field of Business Management. The frequency of use of hedging modal verbs, their main functional uses, and their particular phraseological realizations will be examined. The results will help us gain an insight into how new knowledge claims are negotiated in international English-medium publications in this discipline as well as into the particular shaping of ELF written academic communication.
Keywords: hedges; modal verbs; English for Academic Purposes (EAP); interpersonality; written academic discourse; research article; ELF